Analisis Peluang Serta Tantangan pada Digitalisasi Manajemen Terhadap Filantropi Dakwah di Era Modern - Malikha Cinta Meilany; Mutaji Mutaji; Billgheza Alshakira Bunga; Lulu Nurwidiawati (Pusat Riset dan Inovasi Nasional, 2024)
The digitalization of philanthropic da'wah management has brought about a fundamental change in the way da'wah institutions manage philanthropic activities. By using a digital platform, these philanthropic da'wah institutions can reach a wider audience, increase transparency, and strengthen relationships with donors and the general public. However, this digitalization also brings challenges such as intense competition, demands for high professionalism and accountability, and data security risks. The opportunities for digitalization of philanthropic da'wah management include increasing reach and accessibility, operational efficiency, transparency and accountability, innovation in da'wah programs, and improving relationships with donors. Meanwhile, the challenges faced include intense competition, demands for high professionalism and accountability, and data security risks. Therefore, philanthropic da'wah institutions need to have adaptive and innovative strategies to increase the effectiveness and efficiency of philanthropic da'wah activities in the modern era.